Anti-UV properties of lipidic extracts of three selected marine microalgae - Oliveira, Patrícia (2005)
Today, marine microalgal biomass and their extracts have been incorporated in several cosmetics for skin-care and sun-protecting purposes as well as in some pharmaceutical applications for the therapy of oxidation associated diseases, like inflammations. Some of the bioactive substances are included in the lipidic fraction of microalgae. In the present study we evaluated the potential role of the lipidic extracts from the miroalgae Porphyridium cruentum, Phaeodactylum tricornutum and Nanochloropsis sp., grown in photobioreactors at Necton (Algarve, Portugal). Algal biomass was extracted with hexane:methanol (1:1). The extracts were chemically characterized by TLC and GC-MS and the major fatty acids were identified. The potential role of these extracts in protecting rat skin fibroblast cells from UV-damage was evaluated. Fibroblast cells were irradiated with UV-light (254 nm) for 5 min, a condition that caused significantly cell death after 24 hours (around 40%). When the cells were irradiated in the presence of lipidic extracts of P. cruentum (0.53 mg/ml), P. tricornutum (0.36 mg/ml) and Nanochloropsis sp. (0.57 mg/ml), no cell death was observed. The extracts exhibited poor antiradical properties, as cheeked using DPPH. Taking in account the results, the extracts shown to protect cells from UV-damage but this faculty seems not linked to their antioxidant (namely radical scavenging) properties.